The roots of blue carbon: responses of mangrove stilt roots to variation in soil bulk density. (26th April 2019) - Ola, Anne; Gauthier, Arnault R. G.; Xiong, Yanmei; Lovelock, Catherine E.
Abstract : Mangroves harbour large soil organic carbon (C) pools. These C stocks are attributed to the production and slow decomposition of the below-ground biomass. Novel in-growth containers were used to assess the effect of soil bulk density (BD: 0.4, 0.8 and 1.2 g cm −3 ) on morphological, anatomical and chemical traits of the below-ground fraction of aerial roots of the mangrove Rhizophora stylosa . Dense soils increased total root biomass and primary root diameter, while the primary root length decreased. Furthermore, high soil BD reduced aerenchyma lacunae and led to the formation of structural features such as fibrous strands. These morphological and anatomical changes were not reflected in tissue chemistry, with lignin levels averaging 17.0 ± 0.6%, although roots grown in high BD had higher nitrogen levels. This likely affects decomposition rates. Thus, variation in soil BD has major implications for C sequestration in Rhizophora- dominated mangroves.